2020
DOI: 10.3390/w12082261
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Interventions and Changes in Climate on the Hydro-Chemical Composition of Techirghiol Lake (Romania)

Abstract: The aim of this study is to establish the potential effect of changes in climate and anthropic interventions made over time on the hydro-chemical properties of the Techirghiol Lake. Located in the littoral region of the Black Sea, Techirghiol Lake is the most hypersaline lake of Romania—well-known for the therapeutic properties of the saline water and sapropelic mud. Long-term time series of salinity and water level were investigated in relation to the lake water inputs (precipitation, overland flow and ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The impact of human interventions and climate changes on the hydro-chemical composition of Techirghiol lake (Romania) was recently investigated by Maftei et al 33 . The study identified a degradation of this ecosystem between 1970–1998, due to extensive irrigation in the lake region, followed by a major decrease of the lake’s salinity 33 . Physico-chemical water quality parameters of lake Brăneşti was investigated by Benciu et al 34 .…”
Section: Resultsmentioning
confidence: 99%
“…The impact of human interventions and climate changes on the hydro-chemical composition of Techirghiol lake (Romania) was recently investigated by Maftei et al 33 . The study identified a degradation of this ecosystem between 1970–1998, due to extensive irrigation in the lake region, followed by a major decrease of the lake’s salinity 33 . Physico-chemical water quality parameters of lake Brăneşti was investigated by Benciu et al 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, a multiproxy study of Lake Salda sediment showed that, in the last two millennia before the modern period, the climate variability of the region was mainly influenced by solar forcing [19]. However, with the agricultural intensification in the modern era, human activity overruled the climatic variation in terms of lake levels and salinity [20].…”
Section: Agriculture Datamentioning
confidence: 86%
“…Climatic changes can induce modification of lake surfaces and riverbeds with severe implications for agricultural and economic activities [1][2][3]. The scientific literature demonstrates the "sensitivity" of physical, chemical, and biological lakes' properties to climate change and human intervention [4][5][6]. Since 1960 permanent surface water has been shrinking, drying or has completely disappeared: Aral Lake, Urmia Lake (70% of its surface between 2012-2017 [7]), Chad Lake, Lop Nur, etc.…”
Section: Introductionmentioning
confidence: 99%